Peacebuilding and the rights of indigenous peoples : experiences and strategies for the 21st century - Devere, Heather; Te Maihāroa, Kelli; Synott, John P. (Springer, 2017)
This book analyses efforts to advance the rights of Indigenous People within peace-building frameworks: Section I critically explores key issues concerning Indigenous Peoples' Rights (struggles for land, human, cultural, civil, legal and constitutional rights) in connection with key approaches in peace-building (such as nonviolence, non-violent strategic action, peace education, sustainability, gender equality, cultures of peace, and environmental protection). Section II examines indigenous leaders and movements using peace and non-violent strategies, while Section III presents case studies on the successes and failures of peace perspectives regarding contributions to/ developments in/ advancement of/ barriers to the rights of Indigenous Peoples. Lastly, Section IV investigates what advances have been achieved in Universal Indigenous Peoples' Rights in the 21st century within the context of sustainable peace.
Keywords: Human rights.; Indigenous peoples.; Peace-building.; Humanitarian intervention.; elektronické knihy; electronic books